Controversial and unresolved issues in the treatment of cough in children in outpatient practice - N. A. Geppe; A. B. Malakhov; O. V. Zaytseva; M. V. Degtyareva; N. A. Ilyenkova; O. V. Kalyuzhin; E. P. Karpova; E. S. Kovrigina; N. G. Kolosova; O. I. Simonova; N. D. Soroka; I. P. Shulyak; et al. (Лечащий Врач)
A meeting of the Discussion Club «Controversial and Unresolved Issues in the Treatment of Cough in Children in Outpatient Practice» with the support of the Pediatric Respiratory Society was held in Moscow on September 30 2017, bringing together leading Russian experts in pediatrics, pulmonology, immunology and otorhinolaryngology. There is the experts’ agreed opinion.